Pengaruh Adopsi E-Banking Dan Pengendalian Internal Terhadap Kinerja Keuangan Perbankan Syariah Di Indonesia - Ayuning Tyas, Luluk; Purwanti, Kelita (IAIN Surakarta, 2020)
This study aims to determine the effect of the number of e- banking adoption and internal control on financial performance at Islamic commercial banks in Indonesia. The population in this study is Islamic commercial banks in 2015-2019. The sample of this study is 13 Islamic commercial banks with 65 observations. The sample in this study was taken based on a purposive sampling technique. This research is processed using SPSS 20. The results of this study indicate that the number of e-banking adoption has a negative effect on the financial performance of Islamic banking. Internal control does not have a direct influence on the financial performance of Islamic banking. Keywords: e-banking adoption, internal control, financial performence, islamic commercial banks.